Integrated Policy on the Eradication of Online Gambling Crimes : Case Study in the Jurisdiction of the Surakarta City Police - Elysa Diah Pramesti (Law and Justice research journal, 2025)
This study aims to determine whether the Penal and Non-Penal Integral Policy can be implemented to increase the effectiveness of eradicating online gambling crimes and to determine the obstacles faced by the local government in implementing the Integral Policy on Online Gambling Crimes in Surakarta. This type of research uses empirical legal research, with a descriptive research nature. The research location is at the Surakarta Police, Surakarta City. The types and sources of data in the study consist of two types, primary data and secondary data. Data collection techniques are by observation, interview, and decision study techniques. The results of this study show that the causes of the rampant online gambling in the Surakarta Police area are economic problems, community disobedience to the law, morality factors, low Human Resources (HR), and tradition. The eradication of online gambling in the Surakarta Police area can be said to be effective, although in reality online gambling continues to grow, but during the last five years (2020-2025) there has only been one case file handled regarding online gambling, However, the role of the Police in handling online gambling cases is still limited, so that the perpetrators of gambling are only subject to Article 303 of the Criminal Code concerning gambling. and in handling online gambling cases, there are various obstacles found in the field, both in terms of time, costs and processes that are not easy to imagine.